Policy Cues and Ideology in Attitudes toward Charter Schools. Issue 2 (5th December 2014) - Reckhow, Sarah; Grossmann, Matt; Evans, Benjamin C.
<x xml:space="preserve">Abstract</x> Charter schools have generated support from politicians in both major American political parties while stimulating intense debate among interest groups. We investigate whether and how public attitudes reflect interest group polarization or politician consensus. Using an original survey, we find that charter school opinions diverge along ideological lines among high‐information respondents. With embedded experiments, we manipulate respondents' information using policy cues tied to opposing sides of the charter debate: We assess whether the role of private companies and nonunion teachers changes support for charter schools. We find that the public responds favorably to some informational cues; conservatives without prior information are especially persuaded by information about nonunion teachers. This explains how polarized opinion can develop even in the absence of strong partisan sorting among top political leaders and clarifies the partisan and ideological context of ongoing education policy debates.